2020
DOI: 10.1093/jrr/rraa093
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides extracted fromRheum tanguticumameliorate radiation-induced enteritis via activation of Nrf2/HO-1

Abstract: Radiation-induced enteritis is a major side effect in cancer patients undergoing abdominopelvic radiotherapy. The Nrf2/HO-1 pathway is a critical endogenous antioxidant stress pathway, but its precise role in radiation-induced enteritis remains to be clarified. Polysaccharides extracted from Rheum tanguticum (RTP) can protect the intestinal cells from radiation-induced damage, but the underlying mechanism is unknown. SD rats and IEC-6 cells were exposed to 12 or 10 Gy X-ray radiation. Rat survival, and histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…These findings suggest that the NRF/HO-1 signaling pathway might be important after peroxidative damage of aging. The NRF2/HO-1 signaling pathway can be activated by most phytochemical extracts or their derivatives, including polysaccharides (Zhao et al, 2019;Zhang et al, 2021). Therefore, our findings suggest that the NRF2/HO-1 signaling pathway was crucial in the peroxidative protection of BPS against H 2 O 2 injury.…”
Section: Discussionmentioning
confidence: 66%
“…These findings suggest that the NRF/HO-1 signaling pathway might be important after peroxidative damage of aging. The NRF2/HO-1 signaling pathway can be activated by most phytochemical extracts or their derivatives, including polysaccharides (Zhao et al, 2019;Zhang et al, 2021). Therefore, our findings suggest that the NRF2/HO-1 signaling pathway was crucial in the peroxidative protection of BPS against H 2 O 2 injury.…”
Section: Discussionmentioning
confidence: 66%
“…These results work in with that of Chiang et al ( 2022 ) who observed downregulation of the Nrf2 and HO-1 gene transcription upon intoxication with BPA. Moreover, Zhang et al ( 2021 ) demonstrated that irradiation impedes the protein and gene expression of the Nrf2 and HO-1 via ROS the main mediators of radiation-induced damage, therefore, inducing cell apoptosis and stimulating numerous inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…The precipitates were washed with distilled water and freeze-dried to obtain dried cell debris. The polysaccharides of yeast cells were extracted and determined according to a previously reported method ( Zhang et al, 2021 ). The β-glucan content of polysaccharides was determined using β-glucan assay kits provided by Megazyme International Ireland Limited (yeast and mushroom).…”
Section: Methodsmentioning
confidence: 99%
“…Hericium erinaceus , which grows widely in the mountains of eastern Asia, is a valuable fungus for both medicinal and food use and has a long history in the field of medicine in China. Polysaccharides, the main active substance of H. erinaceus , have high biological activity, such as immunomodulation ( Wu et al, 2019 ; Nowak et al, 2020 ), regulation of glucolipid metabolism ( Du et al, 2015 ; Cai et al, 2020 ), hypolipidemia ( Liang et al, 2013 ), anti -tumor properties ( Zeng and Zhu, 2018 ; Zhang et al, 2021 ), anti-fatigue properties ( Liu et al, 2015 ), liver protection, and stomach protection ( Chen et al, 2020 ). They have also been widely used in medicine ( Li et al, 2018 ; Jithendra et al, 2020 ), materials ( Low et al, 2015 ), cosmetics, and other fields.…”
Section: Introductionmentioning
confidence: 99%